Prevalence of fungi and aflatoxin contamination in stored groundnut in Ghana - Asare Bediako, K.; Dzidzienyo, D.; Ofori, K.; Offei, S.K.; Asibuo, J.Y.; Adu Amoah, R.; Obeng, J. (Food Control, 2019)
Fungal species associated with stored groundnuts together with incidence of aflatoxin contamination in four major growing regions of Ghana were investigated in this study. Aspergillus niger (39.9%)and A. flavus (26.3%)were the predominant species recovered respectively from 73.3% to 83.3% of 60 groundnut samples used for microbial study. A. flavus was found in equal proportion in the four regions under investigation. Other fungal species identified in the study were Colletotrichum (13.3%), Rhizopus (14.8%), Penicillium (5.4%), Curvularia (0.2%)and A. ochraceus (0.1%). A total of 120 samples were assayed for total aflatoxin using HPLC with fluorescence detection. High contamination of groundnut samples (LOD-928.7, mean = 25.0 ng/g)was detected across the four regions with 20.8% exceeding the threshold limit of 20 ng/g total aflatoxin set by the Ghana Standards Authority. A significant positive correlation (0.59, p < 0.01)was observed between A. flavus and total aflatoxin in groundnut samples, an indication that A. flavus was the major causal agent of aflatoxin contamination of groundnut samples in this study. Further, other potential mycotoxigenic fungi were found in groundnut samples suggesting the need to investigate groundnuts in Ghana for contamination by other mycotoxins. © 2019 Elsevier Ltd
Keywords: Aspergillus; Contamination; Fungal species; Groundnut aflatoxin